Seasonal variations in mineral status of reindeer calves from Elgaa reindeer herding district, Norway - Hans Staaland; Stein Sæbø (Rangifer, 1987)
Botanical analyses of rumen content from reindeer calves slaughtered during the period August to April showed dominance of grasses (36%), lichens (30%) and woody plants (21 %). Na content in rumen, bone, liver and muscle samples increased from August to April, whereas K and Mg decreased. It is suggested that the high level of K in summer forage'increases Na excretion and drains the body reserves of this mineral. The body reserves of Na are apparently rebuilt through fall and winter.